2002
DOI: 10.1007/pl00007851
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of botulinum toxin A in upper limb function of hemiplegic patients

Abstract: Botulinum toxin A has been reported to reduce spasticity and increase the comfort of hemiplegic patients. The aim of this study was to assess the efficacy of the treatment on disability, especially in manual activities, and to attempt to identify predictive factors of improvement. Twenty patients (mean age: 54.4 years; M: 14; right hemiplegia: 12) were included, with a delay of at least three months after unilateral hemispheric stroke. Botulinum toxin A (BOTOX) was injected into the arm adductors (8 cases), fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 25 publications
2
33
0
3
Order By: Relevance
“…Antispastic medications, such as botulinum toxin, have been used successfully to reduce muscle spasticity, but their effects on motor functional improvement are still under debate [37][38][39][40]. Antispastic medication usually paralyzes the spastic muscle by disrupting the muscle motor-unit pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Antispastic medications, such as botulinum toxin, have been used successfully to reduce muscle spasticity, but their effects on motor functional improvement are still under debate [37][38][39][40]. Antispastic medication usually paralyzes the spastic muscle by disrupting the muscle motor-unit pathway.…”
Section: Discussionmentioning
confidence: 99%
“…46 Other uncontrolled trials with similar results have reported spasticity reduction in the hemiparetic upper limb without significant functional improvement in global assessment measures. [47][48][49] Interestingly, an exploratory meta-analysis, including two randomized, controlled trials, has revealed that reduction in spasticity was associated with significant improvement in arm function. 50 Combined therapies were also studied in an attempt to enhance the effectiveness of BTX.…”
Section: Btx For Upper Limb Spasticitymentioning
confidence: 99%
“…Despite a decrease in spasticity as measured by the Modified Ashworth Scale, disability as measured by the Rivermead Motor Assessment (RMA) and the Barthel Index (BI) did not improve. Rousseaux and colleagues, 69 however, found improvements in RMA scores but not in Nine-Hole Peg Test scores. Predictive factors for improvement in function may include higher baseline hand function prior to injection.…”
Section: Botulinum Toxinmentioning
confidence: 99%